Rail vehicle impact analysis: A critique of the suitability of the rigid wall model and the assumption of symmetrical behaviour. (February 2015) - Xue, Xiangdong; Robinson, Mark; Schmid, Felix; Smith, Roderick
This paper studies the accuracy of rigid-wall (stonewall) and symmetric models in rail vehicle impact stability. The investigation is based on modelling results and theoretical analysis. The theoretical investigation consists of a mechanical description of the conservation of energy transformation and instability of train impact due to irregular structural collapse and loose coupling patterns. It is shown that an unstable response is a common consequence in vehicle impacts and the corresponding stiffness amongst cross-sections has a strong effect on collapse stability. The modelling investigation summarises impact simulations of a cab vehicle. This illustrates the pitfalls of the rigid-wall and symmetric models as follows: firstly, using a rigid wall in modelling could mask irregular deformations and lead to overestimated crashworthy performance behaviours; and secondly, symmetric impacts could lead to asymmetric deformations resulting in crucial irregular responses of rail vehicles being missed. This paper explores the irregular responses of rail vehicles in train collisions and highlights the relevant issues which might be overlooked when conventional static approaches are used in dynamic scenarios. It is anticipated that the paper will provide increased insight into impact mechanics of rail vehicles and promote a rethink about the influence of characteristic behaviours in dynamic responses resulting in a more accurate representation.